Effects of Moringa oleifera Leaves Powder in Fish Feed Toward Growth Rate and Health of Colossoma macropomum - Safrida Safrida; Nonong Noviasyah; Khairil Khairil (Biosaintifika: Journal of Biology & Biology Education, 2020)
Tambaqui (Colossoma macropomum) is one of freshwater fish that preferred by the community and also in high demand by fish farmers. It has a high selling value and easy to maintain but the growth is slow. One alternative that can be used to improve the fish growth is making rations with the addition of Moringa oleifera leaves. The aim of this study was to determine the effect of Moringa leaves powder on the growth rate and health of C. macropomum. This study used an experimental method with Completely Randomized Design (CRD) with 6 treatments and 4 replications. The data were analyzed using ANOVA Test in Î± =95%. The results showed that P3 with the addition of 30% Moringa leaves powder could increase the growth of Colossoma macropomum. An increase in fish body weight, width, and length was 40.1%, 21.6%, and 6.4% respectively. Â Results of ocular, reflex, and defensive test showed that the fish were in healthy condition compared to their condition before acclimatization. The conclusions of this study is that the addition of Moringa leaves powder in an influential ration can increase the growth and maintain the health of C. macropomum. M. oleifera daily supplement can be used as a substitute for soy flour to promote growth and health of Colossoma macropomum in the seed phase. The addition of M. oleifera can be used as feed supplements to improve the growth and health of Colossoma macropomum.